2015
DOI: 10.1021/acs.biochem.5b00643
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Membrane-Facilitated Release of Nitrite-Derived Nitric Oxide Bioactivity

Abstract: The reduction of nitrite by deoxyhemoglobin to nitric oxide (NO) has been proposed as a mechanism for the transfer of NO bioactivity from the red blood cell (RBC) to the vasculature. This transfer can increase vascular dilatation. The major challenge to this hypothesis is the very efficient scavenging of NO by hemoglobin, which prevents the release of NO from RBCs. Previous studies indicate that the reaction of nitrite with deoxyhemoglobin produces two metastable intermediates involving nitrite bound to deoxyh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…A recent study proposed that only 25% of nitrite is directly reduced into NO, while the rest of the nitrite forms two metastable intermediates of [Fe 2+ Hb···NO 2 − ] and [Fe 3+ Hb-NO ↔ Fe 2+ Hb-NO + ], which holds a >100-fold affinity for the membrane. The proximity of these species to the RBC membrane makes NO release and export possible, which should occur after conformational changes of Hb induced by the presence of the membrane (157). …”
Section: Rbcs and No Metabolismmentioning
confidence: 99%
“…A recent study proposed that only 25% of nitrite is directly reduced into NO, while the rest of the nitrite forms two metastable intermediates of [Fe 2+ Hb···NO 2 − ] and [Fe 3+ Hb-NO ↔ Fe 2+ Hb-NO + ], which holds a >100-fold affinity for the membrane. The proximity of these species to the RBC membrane makes NO release and export possible, which should occur after conformational changes of Hb induced by the presence of the membrane (157). …”
Section: Rbcs and No Metabolismmentioning
confidence: 99%
“…This radical can either oxidize ferrous nitrosylheme to yield the ferric NO-heme derivative (Reaction 4a, Table 3) or react directly with the ferrous hemebound nitric oxide radical to produce N 2 O 3 ( Table 3, Reaction 4b) (78). Both ferric NOHb (via production of either NO + or N 2 O 3 ) (Table 3, Reactions 5b, 5c) (78,153,157) and N 2 O 3 generated from NOHb (Table 3, Reaction 4b) are potential Snitrosating agents that could generate SNOHb, GSNO, and CysSNO. These reactions, subsequent to the NR reaction, are still not fully tested and evaluated.…”
Section: Preserving Transporting and Delivering Hb-derived Nox Bioamentioning
confidence: 99%
“…It was proposed that compartmentalization of NO production in RBCs by formation of protein complexes on the RBC membrane ( e.g ., deoxyHb, AE1/band 3, and Rh-protein channels) facilitates NO production under hypoxic conditions and its export (60). Recently, it was shown that deoxyhemoglobin forms a complex with band 3 on the membrane of RBCs and that the stability of the complex depends on the oxygenation state of hemoglobin (124). Another possibility proposed by us is the presence of specific protein targets within the RBCs, leading to activation of downstream signaling and or protection of NO by local conversion of hemoglobin into methemoglobin (28).…”
Section: No-mediated Luminal Heterocellular Communication: Endotheliumentioning
confidence: 99%